Oral administration of corticosterone at stress-like levels drives microglial but not vascular disturbances post-stroke. (3rd June 2017) - Zalewska, Katarzyna; Ong, Lin Kooi; Johnson, Sarah J.; Nilsson, Michael; Walker, Frederick R.
Highlights: Oral corticosterone delivery at stress-like levels after stroke increases infarct size. Stress-like levels of corticosterone post-stroke alter CD11b expression. Corticosterone administration did not alter the expression of Collagen-IV. Corticosterone is an important stress signal, but is not responsible for all chronic stress effects in post-stroke. Abstract: Exposure to chronic stress following stroke has been shown, both clinically and pre-clinically, to impact negatively on the recovery process. While this phenomenon is well established, the specific mechanisms involved have remained largely unexplored. One obvious signaling pathway through which chronic stress may impact on the recovery process is via corticosterone, and its effects on microglial activity and vascular remodeling. In the current study, we were interested in examining how orally delivered corticosterone at a stress-like concentration impacted on microglial activity and vascular remodeling after stroke. We identified that corticosterone administration for two weeks following stroke significantly increased tissue loss and decreased the weight of the spleen and thymus. We also identified that corticosterone administration significantly altered the expression of the key microglial complement receptor, CD11b after stroke. Corticosterone administration did not alter the expression of the vessel basement membrane protein, Collagen IV after stroke. Together, these results suggest that corticosterone is likely to represent only one of the major stress signals responsible for driving the negative impacts of chronic stress on recovery.